Surviving Southampton : African American women and resistance in Nat Turner's community - Holden, Vanessa M. (Women, gender, and sexuality in American history., 2021)
"The 1831 Southampton Rebellion led by Nat Turner involved an entire community. Vanessa M. Holden rediscovers the women and children, free and enslaved, who lived in Southampton County before, during, and after the revolt. Mapping the region's multilayered human geography, Holden draws a fuller picture of the inhabitants, revealing not only their interactions with physical locations but also their social relationships in space and time. Her analysis recasts the Southampton Rebellion as one event that reveals the continuum of practices that sustained resistance and survival among local Black people. Holden follows how African Americans continued those practices through the rebellion's immediate aftermath and into the future, showing how Black women and communities raised children who remembered and heeded the lessons absorbed during the calamitous events of 1831"--Provided by publisher